Perbandingan Manajemen Persedian Kacang Tanah pada UMKM Kacang Sangrai Ewooww dengan Menggunakan Metode EOQ (Economic Order Quantity) - Surya Kurnia Alamsyah; Faldy Herdian (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. One important aspect in the management of MSMEs is inventory management. This study aims to analyze the best method to control the availability of peanut raw materials in Ewooww Roasted Peanut MSMEs using the EOQ (Economic Order Quantity) method. This research uses a quantitative descriptive approach, and is analyzed using economic order quantity (EOQ), reorder point (ROP),safety stock, and total inventory cost (TIC). Data were collected through direct observation and interviews with MSME owners. The results showed that economic order quantity (EOQ) can streamline inventory costs with the results of the TIC comparison with the EOQ method of Rp.2,745,901 and TIC with the production estimation method (without EOQ) of Rp3,324,992 so that the efficient inventory cost is Rp.579,091 and the reorder point known after EOQ is 1,083kg. The application of the EOQ method can help Ewooww Roasted Peanuts MSMEs in optimizing the management of peanut raw material inventory and increasing operational efficiency.